SISTEM BAGI HASIL PENEMPATAN DANA DENGAN AKAD MUDHARABAH PADA BANK SYARI'AH - Nanan Karyadi; Ni Made Artini (REMITTANCE: JURNAL AKUNTANSI KEUANGAN DAN PERBANKAN, 2020)
Islamic banking operation implements a profit-sharing system or ratio, where the process is both known and approved by the bank and the customer at the time the contract (agreement) is signed. The profit-sharing system carried out by Islamic banks is through dividing the net profit from the business or investment that has been executed. The purpose of this research is to study the provisions of the Mudharabah profit-sharing ratio in Islamic Banks, warnings on the placement of profit-sharing funds in the mudharabah agreement, indicators of the types of mudharabah products in Islamic banks and see what are the benefits of mudharabah. Mudharabah according to Bank BTN Syari'ah is a contract between two parties in which one party called rab'al maal (investor) entrusts money to a second party, called Mudharabah, to carry out a trading business. Mudharib donates his labor and time and their organization according to the terms of the contract. One of the main features of this contract is that the profits will be shared in advance between the investor and the mudarib based on the agreed proposal